Hidroponik Sebagai Alternatif Media Tanam Untuk Peningkatan Kesejahteraan Ekonomi Masyarakat Dalam Tinjauan Ekonomi Islam : Studi Kasus RT 19 Kelurahan Bumiayu Kota Bengkulu - Aprianto Aprianto; Fitri Indah Lestari; Heli Pera Mistika; Kustin Hartini; Andi Harpepen (Lembaga Pengembangan Kinerja Dosen, 2025)
This community service program aims to introduce and implement a hydroponic farming system as an alternative effective planting medium to improve the economic welfare of the community in RT 19, Bumiayu Village, Bengkulu City. This activity is motivated by the limited agricultural land in urban areas and the minimal use of narrow spaces for productive activities. The methods used include counseling, training, and direct practice of hydroponic cultivation by utilizing used goods such as plastic bottles. The results of the activity showed that the community was very enthusiastic in participating in the training and were able to apply basic hydroponic techniques independently. From an Islamic economic perspective, this activity reflects the values ​​of justice, welfare, and empowerment, where the community is not only given knowledge, but also guided to become more economically independent. Hydroponics has proven to be an alternative to modern agriculture that can increase productivity and empower the community in a sustainable manner.